Diagnosis of epithelioid hemangioendothelioma eight days postpartum: Is there a link with pregnancy? A case report and review of the literature. Issue 1 (2nd January 2022) - Somers, Nicky; Creytens, David; Van Belle, Simon; Sys, Gwen; Lapeire, Lore
ABSTRACT: Epithelioid hemangioendothelioma (EHE) is a rare and heterogeneous malignant vascular tumor. Decision making on a treatment strategy is difficult and a standard of care does not exist. EHE shows a wide age distribution but is rare in children. It can appear anywhere in the body, although lung and liver involvement are most common. There is a female predominance for visceral lesions and several case reports in which EHE developed during or after pregnancy are described in literature, hinting towards a putative role of sex hormones in the course of the disease. We present a case of a 32-year-old woman diagnosed with symptomatic pulmonary metastatic hepatic EHE (HEHE) 8 days postpartum, while the patient was completely asymptomatic before. A wait and see policy was chosen and the patient became asymptomatic in the months following the diagnosis. Although no expression of estrogen and progesterone receptors was found in the diagnostic liver biopsy specimen, we presume that the increased level of sex hormones during pregnancy may have triggered disease progression. The clinical behaviour of the disease in this case report reinforces the suspicion of female hormonal involvement in this type of malignancy and hints toward the potential role of other pregnancy-related factors, e.g. placental growth factor (PlGF), in the development of the disease.